5PSQ-114 Improving medication administration for patients with dysphagia. (24th March 2020) - Hosford, J; Mccarthy, S; Silvari, V; Robinson, S
Abstract : Background and importance: Dysphagia affects swallowing not only of food and drink, but also of orally administered medications. Altering solid dose formulations renders administration unlicensed and can adversely affect both patient and administrator, depending on the type of drug. Medication administration in patients with dysphagia necessitates a multidisciplinary approach with no one profession holding all the necessary expertise. Aim and objectives: To improve medication administration for patients with dysphagia. Material and methods: Baseline audit of practice of medication administration to patients with dysphagia (July/August 2016, n=16). Establishment of electronic referral from speech and language therapist (SLT) to pharmacy for patients with dysphagia. Assessment of liquid medications using the International Dysphagia Diet Standardisation Initiative (IDDSI) flow test to enable pharmacists and nursing staff to understand if liquid formulation is suitable for the patient's current fluid recommendations as per SLT. Policy on medication management in patients with dysphagia written and circulated. Ongoing audit of medication administration to patients with dysphagia on wards, and of SLT compliance in completing electronic referral. Audits at 2 months (August 2017, n=14) and at 12 months (August 2018, n=30) post implementation of electronic referral. Results: Median percentage of medications being optimally administered increased from 44% to 89% post implementation of electronic referral and viscosity guide for liquid medications. 40% of patients needing pharmacy review referred by SLT, but 40% of patients needing referral were only highlighted on the day of the audit. Patients were reviewed sooner by pharmacy when electronic referral was completed. Conclusion and relevance: Implementation of SLT electronic referral to pharmacy increased patient safety. The median number of days from SLT assessment to pharmacy review was 0 for patients referred by SLT to pharmacy, compared with a median of 10 days for those not referred. Median percentage of medications optimally administered was 89% per patient in those referred to pharmacy versus 50% in patients not referred. This project has targeted a number of different areas to highlight and improve administration of medication to patients with dysphagia throughout a large acute hospital. The audit cycle continues with the aim of further improving patient care in this area. References and/or acknowledgements: No conflict of interest.